Patient satisfaction at haematology and oncology clinics in the Free State & Northern Cape - W.R. Davies; D.P. Hepburn; M.J. Coetzee; P.N. Badenhorst; L. Goedhals; M. Nel (AOSIS, 2002)
The Free State and Northern Cape make up some 40% of the land area of South Africa, while being home to only 10% of the total population. Haematology and Oncotherapy outreach clinics were established in Kimberley, Bethlehem and Welkom to provide a more accessible service to the thinly spread population. A previous study showed these clinics to be cost-effective, but we had no idea how the patients experience them. Our aim was to obtain information about the demographics of the patients, the logistical support of the clinics, the medical needs of the patients and how they experience the clinics. This can help us to improve the service. A questionnaire was tested in a pilot study. The demographic questions covered age, sex and ethnicity. The logistical questions dealt with distance travelled to the clinic, mode of transport, length of time as a patient and cost. The medical need questions dealt with type of disease, treatment received, type of doctor seen and origin of referral. The questions about experience covered satisfaction with the service, staff, waiting times and involvement of non-governmental organizations. Of the 95 patients interviewed 42% were from the haematology clinics. The mean age was 59.5 and the male: female ratio was 0.6:1. Forty-six percent of the patients spoke Afrikaans and 31 % spoke South Sotho. The black:white ratio was 1:1. Twenty-eight percent used the government ambulances (of whom 80% were satisfied) and 56% used their own cars. The median payment at a clinic was R20 (R0 to R200). Only 19% of patients were paying privately. Ninety-five percent of the patients were follow-ups, with the median length of follow-up being 24 months (1 to 468). The patients were mainly referred by local hospitals. Twentytwo percent of the patients had chronic haematological malignancies, while 68% had solid tumours. Thirty-seven percent of the patients received drugs to take home and only 6% got intravenous chemotherapy. Consultants saw 44% of the patients. The median waiting time to be seen was 1.5 hours (0 to 5). Consultation time averaged 10 minutes and most patients were satisfied with this. Despite the study's small size the system of outreach clinics seems to be delivering a satisfactory service. Criticisms were few. However there were suggestions to create better clinic facilities and to shorten the waiting times at the clinic.